The entrepreneurial intention of university students to venture into business: motivating factors and obstacles - Omar, Siti Sarah; Mahadi, Nomahaza; Ariffin, Zailin Zainal; Wei, Chan Shiaw; Soon, Ng Kim; Yaakop, Azizul Yadi; Muhamad Zin, Fhaizzatul Fharhana (American Scientific Publishers, 2018)
The current unemployment rate in Malaysia among graduates is distressing despite the increase of interest of becoming entrepreneurs among students. The call for graduates to create job instead of look for job has just been launched recently by the Ministry of Higher Education Malaysia. Thus this study is attempted to identify the dominant motivating factor and obstacle among final year students in a higher learning institution to become entrepreneurs. Besides, this study investigates the relationship between motivating factors and entrepreneurial intention among them. Respondents were final year students of eight faculties; with the sample size of 324 students out of 2081 students from the total population. This study employs quantitative method by using questionnaire and data were analysed by using the latest version of Statistical Package for Social Sciences. The results show that behavioural control (self-efficacy beliefs) is the dominant motivating factor (mean value = 4.07) meanwhile skills is a dominant of obstacle (mean value = 3.74). The Spearman’s rho correlation coefficient is r(218) = 0.633, p < 0.05 (p = 0.000) which shows that there is a strong relationship between the motivating factor and the entrepreneurial intention.